Venomics of the milos viper (Macrovipera schweizeri) unveils patterns of venom composition and exochemistry across blunt-nosed viper venoms - Schulte, Lennart; Damm, Maik; Avella, Ignazio; Uhrig, Lilien; Erkoc, Pelin; Schiffmann, Susanne; Fürst, Robert; Timm, Thomas; Lochnit, Günter; Vilcinskas, Andreas; Lüddecke, Tim (Frontiers in Molecular Biosciences, 2023)
Introduction: Snakebite is a neglected tropical disease and a globally important driver of death and morbidity. Vipers of the genus Macrovipera (Viperidae: Viperinae) are among the snakes of higher medical importance in the Old World. Despite the medical relevance of Macrovipera venoms, the knowledge regarding them is heterogeneously distributed with virtually all works conducted so far focusing on subspecies of Macrovipera lebetinus, while other species within the genus are largely overlooked. Here we present the first proteomic evaluation of the venom from the Greek endemic Milos viper (Macrovipera schweizeri). In line with clinical symptoms typically elicited by Macrovipera envenomations, Milos viper venom primarily comprises coagulotoxic and cytotoxic protein families, such as metalloproteinases (svMP) and serine proteases (svSP). Methods: We conducted comparative bioactivity assays on venoms from M. schweizeri and the M. lebetinus subspecies M. lebetinus cernovi, M. lebetinus obtusa, and M. lebetinus turanica, and showed that they all exhibit similarities in levels of cytotoxicity proteolytic activity, and inhibition of prokaryotic growth. Lastly, we compared Macrovipera venom profiles by 1D-SDS-PAGE and RP-HPLC, as well as our proteomic data with previously published Macrovipera venom proteomes. Results and discussion: The analyzes performed to reveal that a general venom profile seems to be conserved across blunt-nosed vipers, and that, M. schweizeri envenomations, similarly to those caused by other blunt-nosed vipers, are able to cause significant tissue damage. The present work represents an important starting point for the development of comparative studies across the full taxonomic range of the genus Macrovipera and can potentially help optimize the treatment of envenomations caused by M. schweizeri.